The internationalization of Muslim Chinese ummah during the Tang Dynasty - Azlizan Mat Enh,; Suffian Mansor, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The historical ties between Muslim and Chinese cultures hold a significant position in Asian geopolitics and have left an indelible mark on world history. During the Tang Dynasty, the spread of Islam, the flourishing Silk Road, and enhanced communication between China and foreign nations facilitated the migration of numerous Muslim merchants, envoys, and missionaries from Arabia and Persia to China. These Muslim ummah became central to foreign trade, connecting China with the Western world through Southeast Asia and the Indian Ocean. This period represents one of the most remarkable chapters in Chinese history, with Muslim activities during the Tang Dynasty profoundly shaping the nation’s historical and cultural development. This study aims to systematically explore the history of Muslims ummah during the Tang Dynasty in China by utilising textual analysis and examining historical sites. The research provides a foundational framework for further investigations into the enduring influence of Chinese Muslim ummah history, highlighting its significance in the broader narrative of global historical interactions.